1998
DOI: 10.1007/bf02744935
|View full text |Cite
|
Sign up to set email alerts
|

Human pregnancies after transfer of fresh (four-to eight-cell) versus frozen-thawed blastocysts resulting from intracytoplasmic sperm injection

Abstract: Purpose: The objective of this stud), was to obtain expanded blastocysts .following intracytoplasmic sperm injection (ICSI) and Vero-cell co-culture, cpyopreserve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our earlier reports demonstrated that ICSI of frozen-thawed spermatozoa immobilized by aggressive abrasion of tails could fertilize mature bovine and caprine oocytes better than those injected intact [11,12]. Indeed, immobilization of sperm tails before human ICSI enhances success of this infertility treatment [14,31]. This has been attributed to faster sperm membrane dissolution and intermingling of the sperm nucleus with the oocyte's cytoplasm [32].…”
Section: Discussionmentioning
confidence: 97%
“…Our earlier reports demonstrated that ICSI of frozen-thawed spermatozoa immobilized by aggressive abrasion of tails could fertilize mature bovine and caprine oocytes better than those injected intact [11,12]. Indeed, immobilization of sperm tails before human ICSI enhances success of this infertility treatment [14,31]. This has been attributed to faster sperm membrane dissolution and intermingling of the sperm nucleus with the oocyte's cytoplasm [32].…”
Section: Discussionmentioning
confidence: 97%